Ensuring development efficiency with DevSecOps: A case study on streamlining dependency vulnerability management with Dependabot - Laitinen, Aatu Kalevi (2024)
With the ever increasing need for modern software development companies to be able to continuously release new code and the increased emphasis on the security of the software, the practice of shifting security processes to the earlier stages of the development has become coveted. However creating a DevSecOps environment where the responsibility of the security processes is shifted to the developers without hindering their ability to efficiently produce software is challenging.